Dimensionality of organizational citizenship behavior (OCB) in a multicultural society the case of Malaysia - Lo, May-Chiun; Ramayah, T. (International Business Research, 2009)
Past researches have observed a shift in the dimensions of organizational citizenship behavior. Building on organizational citizenship behavior literature, the present study in the paper involved looking at validating the dimensionality of the organizational citizenship behavior (OCB) measure developed by Organ (1988) who posited a five dimension instrument. Data was gathered through a survey using a structured questionnaire to employees working in 10 large manufacturing companies in Malaysia. A total of 113 questionnaires were returned over a period of 10-week. A series of tests such as factor analysis, correlation, and reliability analysis was conducted to confirm that the instrument is valid (content, construct, convergent, discriminant and nomological) as well as reliable. Implications regarding the value of conducting validity and reliability test for practitioners and researchers are discussed.